Ventricular Myocardial Function and Central Hemodynamics in Patients with Secondary Atrial Septal Defect and Persistent or Paroxysmal Atrial Fibrillation - Petkanych, Myroslav M.; Potashev, Sergiy V.; Bankovska, Nataliia V.; Lazoryshynets, Vasil V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Background. Atrial fibrillation (AF) is the world’s most frequent arrhythmia associated with significant morbidity and mortality. Non-invasive multimodal imaging provides all necessary information for tactical decisions about radiofrequency catheter ablation and other methods of pharmacological and invasive AF treatment. Survival of patients with congenital heart diseases (CHDs) has grown over the past years. Still, there is a significant gap in evidence-based data regarding management of such patients with AF. Previously in Ukraine there were no studies of echocardiography parameters in patients with CHDs with paroxysmal or persistent AF, namely, those to find predictors for successful AF treatment before atrial septal defect (ASD) surgical or percutaneous closure. The aim. To evaluate ventricular myocardial function and central hemodynamics in patients with secondary ASD and paroxysmal or persistent AF compared to patients with paroxysmal or persistent AF without CHD. Methods. Weexamined54patients(36[66.7%]menand18[33.3%]women)aged61.4±9.8yearswithsecondaryASDand paroxysmal or persistent AF. Control group included 56 patients (38 [67.9%] men and 18 [32.1%] women) without CHD with non-valvular paroxysmal or persistent AF. All the patients underwent transthoracic and transesophageal echocardiography with tissue Doppler imaging and speckle-tracking echocardiography for longitudinal myocardial strain evaluation. Results. The patients in the study and control groups were comparable in terms of age and gender as well as comorbidities and cardiovascular risk factors. There were significant differences in the left heart remodeling indices and central hemodynamics alteration grades, for instance, the patients of the study group had significantly higher grade of left ventricular (LV) hypertrophy. Patients with ASD also had significantly more dilated LV and left atrium (LA) cavities and higher combined indices of LV filling pressure – E/E’ (14.9±4.2 vs. 9.6±5.3, p<0.0001) and E/Vp (2.84±0.44 vs. 2.25±0.61, p<0.0001), explaining more frequent AF in patients with ASD. The study group patients also had significantly higher systolic (sPAP) (52.4±2.8 vs. 44.6±3.2, p<0.0001) and mean (mPAP) (38.6±4.3 vs. 31.7±1.9, p<0.0001) pulmonary artery pressure compared to control group, as well as significantly worse all known indices of right ventricle (RV) myocardial function and right chambers overload. Global RV longitudinal strain strongly correlated with RV fractional area change (r = 0.75; p<0.0001), and especially highly with tricuspid annular plane systolic excursion (r = 0.97; p<0.0001) and tricuspid annular peak systolic velocity S’ (r = 0.98; p<0.0001) during tissue Doppler imaging, making it trustworthy and valuable predictor of RV myocardial dysfunction and its potential restoration after defect correction. Patients with ASD much more often had significant moderate-to-severe functional tricuspid regurgitation (92.6% vs. 53.4%, p<0.0001) with significantly higher central venous pressure indices (16.4±2.4 vs. 10.2±2.5, p<0.0001) as per significantly wider inferior vena cava (IVC) (1.89±0.31 vs. 1.43±0.42, p<0.0001) and it’s higher inspiratory collapse. IVC diameter strongly correlated with integral RV filling pressure (that is, right atrial pressure) index E/E’ (r = 0.98; p<0.0001). Also, study group demonstrated significantly more frequent LA appendage thrombosis (40.7% vs. 21.4%, p=0.029) along with much more marked spontaneous contrast phenomenon and lower LA appendage expulsion rate (26.7±5.1 vs. 34.3±7.2, p<0.0001). Conclusions. Stratification of patients with ASD complicated by paroxysmal or persistent AF for radiofrequency catheter ablation requires thorough echocardiographic examination with targeted certain indices evaluation aiming at earlier intervention in order to earlier diagnosis and invasive or surgical treatment in this specific patient group, namely LV hypertrophy grade, left chambers dilation with LV global systolic function evaluation, pulmonary hypertension grade as per sPAP and mPAP evaluation, as well as combined right chambers overload grade indices, including RV myocardial function by all methods including speckle-tracking echocardiography.